PENGARUH CAMPURAN BAHAN BAKAR GASOLINE DAN PERTALITE TERHADAP TINGKAT POLUSI GAS BUANG TERHADAP MESIN HONDA 125 CC - ADNAN SURBAKTI (JSIK (Jurnal Sistem Informasi Kaputama), 2019)
The purpose of this study is to distinguish exhaust gas emissions (CO and HC) from a 125 cc motorcycle mixed with Gasoline and pertalite (75% -25%) with Gasoline fuel. The method used is the expriment method, namely by conducting a direct experiment. The material and tools used are a supra x 125 motorbike, gas analyzer, Gasoline, pertalite. The results of the research are obtained for a mixture of pertalite and Gasoline (75% -25%). For 1000 rpm rotation, the CO price is 3.0 and the price HC is 120, for round 2000 rpm the price of CO is 2.95, and the price of HC is 112, for 3000 rpm the price of CO is 2.87, and the price of HC is 110. for 4000 rpm, the price of CO is 2.65 and HC price is 100. The research results can be for mixture (50% -50%). For 1000 rpm rotation, CO price is 3.15 and HC HC price is 130, for 2000 rpm round, CO price is 3.01, and price HC is 124, for 3000 rounds rpm CO is 2.96, and HC price is 120, for 4000 rpm rotation, CO price is 2.75, and HC is 119. Research result (100%). For 1000 rpm rotation CO price is 4.1, and HC price is 160, for round 2000 rpm, price of CO 3.95 and HC is 152, for round 3000 rpm, price of CO is 3.70, and price of HC is 145, for rotation of 4000 rpm, the price of CO 3.55 and HC is 140. In conclusion, the higher the rotation, the greater the HC both the mixture of gasoline and pertalite and gasoline are smaller, while for CO, if the rotation is greater then the percentage is smaller for a mixture of gasoline and pertalite, and pertalite the price is more expensive.Keywords: Supra X 125, Pertalite, Gasoline and Gas Analyzer